2005
DOI: 10.1158/0008-5472.can-04-1357
|View full text |Cite
|
Sign up to set email alerts
|

BCR-ABL Induces the Expression of Skp2 through the PI3K Pathway to Promote p27Kip1 Degradation and Proliferation of Chronic Myelogenous Leukemia Cells

Abstract: Chronic myelogenous leukemia (CML) is characterized by the expression of the BCR-ABL tyrosine kinase, which results in increased cell proliferation and inhibition of apoptosis. In this study, we show in both BCR-ABL cells (Mo7e-p210 and BaF/3-p210) and primary CML CD34+ cells that STI571 inhibition of BCR-ABL tyrosine kinase activity results in a G 1 cell cycle arrest mediated by the PI3K pathway. This arrest is associated with a nuclear accumulation of p27Kip1 and down-regulation of cyclins D and E. As a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
2
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 55 publications
8
92
2
3
Order By: Relevance
“…We compared this effect with that of the Bcr-Abl1-kinase inhibitor IM. As earlier reported (Andreu et al, 2005), IM also increases the level of hypo-phosphorylated Rb, finally inducing the disappearance of the hyper-phosphorylated forms of the protein (Figure 4a). …”
Section: Btz Inhibits Proliferation Of Bcr-abl1-expressing Cellssupporting
confidence: 86%
See 3 more Smart Citations
“…We compared this effect with that of the Bcr-Abl1-kinase inhibitor IM. As earlier reported (Andreu et al, 2005), IM also increases the level of hypo-phosphorylated Rb, finally inducing the disappearance of the hyper-phosphorylated forms of the protein (Figure 4a). …”
Section: Btz Inhibits Proliferation Of Bcr-abl1-expressing Cellssupporting
confidence: 86%
“…It is known that these two proteins are among the many factors that regulate the levels and activity of the cell-cycle inhibitors p21Cip1 and p27Kip1 (Perez-Roger et al, 1999;Kossatz et al, 2004). On the other hand, Bcr-Abl1-kinase activity inhibition with IM results in the downregulation of both Skp2 and c-Myc, indicating that these two proteins are molecular targets of Bcr-Abl1 (Sawyers, 1993;Andreu et al, 2005). Therefore, we analyzed the effect of Btz on Skp2 and c-Myc and found that both show lower levels in Btztreated cells expressing Bcr-Abl1, with no significant change in BaF/3 control cells (Figure 5b).…”
Section: Btz Prevents the Activation Of Nf-kbmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect was dependent on the upregulation of the CDK inhibitor p27 KIP1 in the nuclear compartment as demonstrated by siRNA-mediated depletion of p27 KIP1 , which prevented the effects of imatinib on BrdU incorporation. Regulation of p27 KIP1 protein levels is mainly achieved by ubiquitin dependent proteolysis [27,33]; however, increased p27 KIP1 mRNA levels in imatinib-treated cells have been described [34]. Real-time PCR assays ruled-out increased p27 KIP1 mRNA levels in neuroblastoma cells exposed to imatinib.…”
Section: Discussionmentioning
confidence: 99%